Dual-release Hydrocortisone in Addison’s Disease – A Review of the Literature - Giordano, Roberta (Eur Endocrinol, 2014)
In patients with adrenal insufficiency, glucocorticoids (GCs) are insufficiently secreted and GC replacement is essential for health and, indeed, life. Despite GC-replacement therapy, patients with adrenal insufficiency have a greater cardiovascular risk than the general population, and suffer from impaired health-related quality of life. Although the aim of the replacement GC therapy is to reproduce as much as possible the physiological pattern of cortisol secretion by the normal adrenal gland, the pharmacokinetics of available oral immediate-release hydrocortisone or cortisone make it impossible to fully mimic the cortisol rhythm. Therefore, there is an unmet clinical need for the development of novel pharmaceutical preparations of hydrocortisone, in order to guarantee a more physiological serum cortisol concentration time-profile, and to improve the long-term outcome in patients under GC substitution therapy.